2005
DOI: 10.1111/j.1600-0501.2005.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma and fibrin as delivery systems for recombinant human bone morphogenetic protein‐2

Abstract: The aim of the present study was (1) to test whether or not platelet-rich plasma (PRP) or commercially available fibrin can increase bone regeneration compared with non-treated defects and (2) to test whether or not PRP or fibrin increases bone regeneration when used as a delivery system for recombinant human bone morphogenetic protein-2 (rhBMP-2). In 16 New Zealand White rabbits, four evenly distributed 6 mm diameter defects were drilled into the calvarial bone. The following five treatment modalities were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 37 publications
0
56
0
6
Order By: Relevance
“…134 However, no statistically significant differences of platelet growth factor release was seen after combined implantation of rabbit PRP/BMP-2 gels compared to fibrin/BMP-2 gels in rabbit cranial defects. 135 Moreover, in a clinical trial, the combination of PRP and BMP has shown to be even less effective than BMPs alone. 136 In addition to the variation in experimental setups between these studies, growth factor concentrations in PRP are known to be variable between species and individuals, 137 all adding to the confusion around effectivity of PRP and combinations with BMPs.…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…134 However, no statistically significant differences of platelet growth factor release was seen after combined implantation of rabbit PRP/BMP-2 gels compared to fibrin/BMP-2 gels in rabbit cranial defects. 135 Moreover, in a clinical trial, the combination of PRP and BMP has shown to be even less effective than BMPs alone. 136 In addition to the variation in experimental setups between these studies, growth factor concentrations in PRP are known to be variable between species and individuals, 137 all adding to the confusion around effectivity of PRP and combinations with BMPs.…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…Another probable explanation may be the nature of the scaffold, which is autogenous or alloplastic. Additional use of PRP in autogenous bone scaffold stimulates osteogenesis by releasing several growth factors contained in PRP stimulating angiogenesis and the proliferation of osteoprogenitor cells only in the early period after transplantation; conversely, PRP has no positive effect on osteogenesis when used with alloplastic or xenogenic scaffolds (26). Moreover, PRP highly varies from donor to donor, and each PRP preparation can differ in its concentration of proteins and growth factors (27).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin gel appears to closely mimic a blood clot, without the inherent propensity of the latter to discolor the tooth. It is a material that can be modified easily to suit the application and has been approved by Food and Drug Administration [39]. Compared to other hydrogels it shows better results in cell proliferation and differentiation [40].…”
Section: Discussionmentioning
confidence: 99%